4.7k views
5 votes
. Find the inverse of each function.

a. f(x) = 2x−3
b. g(x) = 2 log(x − 1)
c. h(x) = ln(x) − ln(x − 1)
d. k(x) = 5 − 3^−x/2

User Tikkaty
by
4.5k points

1 Answer

3 votes

Answer:

a.
f^(-1)(x)=(x+3)/(2)

b.
g^(-1)(x) =e^{(x)/(2)}+1

c.
h^(-1)(x)=(e^(y))/(e^(y)-1)

d.
k^(-1)(x)=-(2log(5-y))/(log(3))

Explanation:

Here is the procediment for each case.

a.
f(x)=2x-3 as we know
f(x)=y then
y=2x-3 finding the expresion of x, we find the inverse of the function, then:


y=2x-3\\y+3=2x\\\\(y+3)/(2)=x

Then:


f^(-1)(x)=(x+3)/(2)

b.
g(x)=2log(x-1) for this we have to remember that the inverse function of the log is the exp, then:


g(x) = 2 log(x-1)\\y=2log(x-1)\\\\\\(y)/(2)=log(x-1)\\\\e^{(y)/(2)}=e^(log(x-1))\\\\e^{(y)/(2)}=x-1\\e^{(y)/(2)}+1=x

Then the inverse function is:


g^(-1)(x) =e^{(x)/(2)}+1

c. In this case we have to also remember the relation between the e and the ln, then:


h(x) = ln(x)-ln(x-1) with the properties of the ln we have:


h(x) = ln(x)-ln(x-1)=ln\left((x)/(x-1)\right) now finding the inverse function we have:


h(x)=ln\left((x)/(x-1)\right)\\\\y=ln\left((x)/(x-1)\right)\\\\e^(y)=e^{ln\left((x)/(x-1)\right)}\\\\\\e^(y)=(x)/(x-1)}\\\\e^(y)(x-1)=x\\e^(y)x-e^(y)=x\\e^(y)x-x=e^(y)\\x(e^(y)-1)=e^(y)\\x=(e^(y))/(e^(y)-1)

then:


h^(-1)(x)=(e^(y))/(e^(y)-1)

d. in the last one we have:
k(x) =5-3^(-x/2) then:


k(x) =5-3^(-x/2)\\y =5-3^(-x/2)\\y-5=-3^(-x/2)\\5-y=3^(-x/2)\\log(5-y)=log(3^(-x/2))\\log(5-y)=-(x)/(2)log(3)\\-2log(5-y)=xlog(3)\\-(2log(5-y))/(log(3))=x

then:


k^(-1)(x)=-(2log(5-y))/(log(3))

User Kaajal
by
4.8k points